Antimicrobial Susceptibility Testing of Mycobacterium bovis Isolates from Michigan White-Tailed Deer during the 2009 Hunting Season - Scott D. Fitzgerald; Angie M. Schooley; Dale E. Berry; John B. Kaneene (Veterinary Medicine International, 2011)
Michigan has had an ongoing outbreak of endemic Mycobacterium bovis which has been recognized within and sustained by its free-ranging white-tailed deer population since 1994. Worldwide, organisms within the Mycobacterium tuberculosis complex have exhibited the ability to develop resistance to antimicrobial agents, resulting in both the multidrug-resistant (MDR) and extensively drug-resistant (XDR) strains of human tuberculosis. Michigan's Bovine Tuberculosis Working Group has conducted active antimicrobial susceptibility testing on wildlife isolates of the endemic M. bovis organism at five-year intervals to detect any emerging drug resistance patterns. The results of 33 white-tailed deer origin isolates collected from the 2009 hunting season are reported here. There continues to be no evidence of any drug resistance except for pyrazinamide resistance. These results are likely due to the lack of antibacterial treatment applied to either wildlife or domestic animals which would provide selection pressure for the development of drug resistance.